UNVEILING THE RICH AQUATIC FLORA AND FAUNA OF SANTIJAN BEEL, ASSAM, INDIA - ARUP JYOTI BORA; ASHOK KUMAR BORA (The Bioscan, 2024)
Due to the urbanization, industrialization, advancement of the technological activities, uses of chemical fertilizers, pesticides and insecticides are showing the big threatening to the natural environment. Among the natural features, the water bodies specially the rivers, streams, wetlands suffer most from the human induced activities and resultant actions. Wetlands are the most important element of the biotic world which provide shelter for enormous aquatic species and other living organisms. In the recent years, many study take place for the conservation and measuring the degradation of the wetland ecology. This paper is an attempt to discuss the present scenario of the aquatic floral and faunal species and give a brief knowledge about the richness of the Santijan beel ecology in Nagaon district, Assam. For better understanding and collection of proper data, and analysing these in a good manner a primary filed survey was conducted. The findings of the study disclose that the Santijan is rich in aquatic ecosystem and ecological diversity at the present day context and should be proper managed and conserved.